Visible-light induced green synthesis of γ-deuterated carbonyl compounds. (6th July 2022) - Hu, Lifu; Li, Ruining; Deng, Wei; Sun, Zhankui
Graphical abstract: Abstract: Deuteration is a widely used labelling technique. Through a visible-light induced desulfurization and radical addition process in EtOAc-D2 O, we were able to develop the direct synthesis of γ-deuterated carbonyl compounds from α-sulfide ketones and alkenes. Products with different functionalities were efficiently synthesized with high-deuteration. This mild and metal-free method provides a valuable tool for medicinal and synthetic chemists.